2015
DOI: 10.3945/ajcn.114.088328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mastication on lipid bioaccessibility of almonds in a randomized human study and its implications for digestion kinetics, metabolizable energy, and postprandial lipemia

Abstract: Background: The particle size and structure of masticated almonds have a significant impact on nutrient release (bioaccessibility) and digestion kinetics.Objectives: The goals of this study were to quantify the effects of mastication on the bioaccessibility of intracellular lipid of almond tissue and examine microstructural characteristics of masticated almonds.Design: In a randomized, subject-blind, crossover trial, 17 healthy subjects chewed natural almonds (NAs) or roasted almonds (RAs) in 4 separate mastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
150
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(163 citation statements)
references
References 43 publications
11
150
1
1
Order By: Relevance
“…In addition, a meta-analysis of clinical trials reported that nut consumption was associated with non-significant decreases in body weight (0.47 kg), BMI (0.40 kg/m 2 ), and waist circumference (1.25 cm) [34]. The lack of weight change with regular nut consumption may be explained by dietary compensation, inefficient energy absorption, and an increase in metabolic rate [27,28,34,59,60]. While collectively these data indicate that adding nuts to the diet does not result in weight gain, it should be noted that this research emphasises the inclusion of whole nuts into the diet, and this information should not be extrapolated to nuts in the form of snack bars and confectionery products.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a meta-analysis of clinical trials reported that nut consumption was associated with non-significant decreases in body weight (0.47 kg), BMI (0.40 kg/m 2 ), and waist circumference (1.25 cm) [34]. The lack of weight change with regular nut consumption may be explained by dietary compensation, inefficient energy absorption, and an increase in metabolic rate [27,28,34,59,60]. While collectively these data indicate that adding nuts to the diet does not result in weight gain, it should be noted that this research emphasises the inclusion of whole nuts into the diet, and this information should not be extrapolated to nuts in the form of snack bars and confectionery products.…”
Section: Discussionmentioning
confidence: 99%
“…However, the oil bodies and the endoplasmic network were largely destroyed, and the volume of extracellular pores enlarged. Roasting can therefore greatly affect the structure of almond cells, the cell walls as well as the intra‐cellular oil bodies (Pascual‐Albero et al ., ; Varela et al ., ; Mandalari et al ., ; Grundy et al ., ,b). In these studies, roasted almond oil bodies appeared to coalesce to form larger oil droplets than the ones observed in raw almond cells.…”
Section: Processing Techniques and Their Impact On Almond Structurementioning
confidence: 97%
“…The roasted almonds used in our recent studies (Grassby et al ., ; Mandalari et al ., ; Grundy et al ., ,b, ) were provided by the Almond Board of California and were roasted using a two‐step standard procedure of hot air roasting with typical temperatures ranging from ~130 to 154 °C (Almond Board of California, ). The first step employed an intermediate temperature to stabilise the nut microstructure, and the second step was performed at a higher temperature in order to generate the distinctive roasted flavour and brown colour of the cotyledon.…”
Section: Processing Techniques and Their Impact On Almond Structurementioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reported reasons for this less-than-predicted weight gain observed with the inclusion of nuts into the regular diet. These include an increase in satiety due to the protein and fibre content of nuts; an increase in energy expenditure due to the high unsaturated fat content; and loss of energy in the faeces as a result of the indigestibility of the cell wall and/or incomplete mastication [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%